ANALISIS PRODUKTIVITAS MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) STUDI KASUS PADA PT XYZ - Sudri, Ni Made; Mareti, Amalia (Teknik dan Ilmu Komputer, 2012)
The effectiveness of facility had been directly influenced to the competitive level and business advantage. Looking for the tools of effectiveness could be used the overall equipment effectiveness (OEE) method. The measurement of performance on PT XYZ by OEE method had been taken that OEEÃ¢â¬â¢s value has still lower, particularly caused by the lower values on rate of productÃ¢â¬â¢s quality and performanceÃ¢â¬â¢s value rate. For increasing those values the problems that consist is ÃÂ holeÃ¢â¬â¢s reject, hideÃ¢â¬â¢s reject, and disputed reject could be done by standard dies component, trying of trial and error of core design until precision on both sides, and installing sensor on temperatureÃ¢â¬â¢s indicator device had been stable the temperature.ÃÂ ÃÂ Keywords: overall equipment effectiveness (OEE) method, rate of quality product, performanceÃ¢â¬â¢s value rateÃÂ